EDUKASI GIZI UNTUK PENCEGAHAN KEKURANGAN ENERGI KRONIK (KEK) PADA IBU HAMIL DI DESA BEKONANG SUKOHARJO - Ahmad Rifai; Amanda Permata Putri Putri; Yasier Ikrom; Siti Rahma Fatkhiyah; Devina Kemala Pratidina; Qur'ana Fauziyah; Fauziah Nurulita Addin; Nadiah Ardiningrum; Umi Budi Rahayu; Fitriana Mustikaningrum (Universitas Muhammadiyah Surakarta, 2026)
Chronic Energy Deficiency (CED) in pregnant women is a nutritional issue that directly contributes to increased maternal and infant morbidity and mortality rates, as well as the overall quality of future generations. Bekonang Village, located in Mojolaban Sub-district, Sukoharjo Regency, is one of the areas still facing significant challenges in preventing CED, as indicated by the low awarene ss among pregnant women regarding the importance of balanced nutrition during pregnancy. This community service activity aimed to improve pregnant women’s knowledge about CED and its prevention through structured and communicative nutrition education. The method consisted of nutrition counseling delivered through interactive lectures, discussions, and leaflet distribution to 30 pregnant women. Knowledge levels were assessed using pre-test and post-test instruments to evaluate the effectiveness of the intervention. The results showed a significant increase in knowledge scores after the educational session, indicating the success of the educational approach used. Additionally, participants demonstrated high levels of enthusiasm and active engagement, which contributed to achieving the program’s objectives. Target ed and participatory nutrition education has proven to be an effective strategy for supporting CED prevention at the community level. This activity is expected to serve as a promotive and preventive model that can be replicated in maternal health programs in other regions.